Improving Arabica Coffee Quality Using Anaerobic Carbonic Maceration Techniques in East Lombok Regency - Sari Novida; Narita Amni R; Nirmawati (Postgraduate, University of Mataram, 2025)
There are various post-harvest coffee techniques to improve quality, one of which is the anaerobic technique of carbonic maceration method. The research objectives are to know the process of improving the quality of arabica coffee quality through anaerobic semi carbonic maceration technique; to know the taste of arabica ground coffee after using anaerobic semi carbonic maceration technique. This research method is experimental with the aim of seeing the quality of coffee beans produced from the semi-carbonic maceration technique. Based on the research results, the anaerobic semi-carbonic maceration coffee fermentation engineering technique was successfully carried out in Sajang Village, Sembalun District, East Lombok Regency for 2 months. Based on the results of research and favorability tests on 30 respondents by comparing coffee produced from anaerobic semi-carbonic maceration techniques and natural processes, the following results were obtained: Arabica coffee using anaerobic semi-carbonic maceration technique received a score of 4.71 for aroma, score of 4.53 for flavor, score of 4.16 for body and score of 4.20 for sweetness. Arabica coffee brewed with anaerobic semi-carbonic technique is more favored by consumers compared to natural arabica coffee brewing technique.